Second-dose measles vaccination and associated factors among under-five children in urban areas of North Shoa Zone, Central Ethiopia, 2022 - Tadesse, Addisu Waleligne; Sahlu, Degemu; Benayew, Mengistu (Frontiers in Public Health, 2022)
Introduction Measles remain a leading cause of vaccine-preventable infant mortality. In Africa, about 13 million cases and 6,50,000 deaths occur annually, with Sub-Saharan Africa having the highest morbidity and mortality. Ethiopia launched second-dose measles vaccination into the routine immunization program in the second year of life in 2019. However, little has been known about the coverage of the second-dose measles vaccine. Therefore, the purpose of this study was to assess the level of second-dose measles vaccine uptake and associated factors in North Shoa Zone, Central Ethiopia. Objective To assess second-dose measles vaccination and associated factors among under-five children and to identify reasons for not being vaccinated in urban areas of North Shoa Zone, Central Ethiopia, 2022. Method A community-based cross-sectional study was conducted from 1 February to 15 March 2022. The sample size was 410, and it was allocated proportionally to each kebelle. The study units were selected consecutively. The data were collected using structured interviewer-administered questionnaires. Four nurses were used as data collectors. Data were coded manually and entered into Epi-data Version 4.4.2.1. Frequency and cross-tabs were used for data cleaning. Data were analyzed using SPSS Version 21 software. Multicollinearity and model goodness-of-fit tests were checked. A multivariable logistic regression model at 95% CI was used to identify factors associated with the dependent variable. Result The response rate was 90.7%. The level of second-dose measles vaccination among children in urban areas of North Shoa Zone was 42.5% [95% CI (36.8, 47.3)]. Maternal age of ≤ 25 years [AOR = 9.12: 95% CI (1.97, 42.19)], 26–30 years [AOR = 9.49: 95% CI (2.33, 38.63)], 31–35 years [AOR = 7.87: 95% CI (1.78, 34.79)]; average time mothers had been waiting for vaccination at the health facility [AOR = 3.68: 95% CI (1.33, 10.23)]; awareness about vaccine-preventable diseases [AOR = 4.15: 95% CI (1.53, 11.26)]; and awareness on recommended measles doses [AOR = 17.81: 95% CI (3.91, 81.22)] were identified as factors associated with MCV2 vaccination. The major reason (48.1%) reported by mothers for not vaccinating second-dose measles vaccine was being unaware of the need to return for second-dose measles vaccination. Conclusion and recommendation The level of second-dose measles vaccination (MCV2) among children in urban areas of the North Shoa Zone was low. Maternal age, average time mothers had been waiting for vaccination at the health facility, awareness about vaccine-preventable diseases, recommended age for the last vaccination, and recommended measles doses were identified as factors associated with MCV2 uptake. The major reason for not vaccinating MCV2 was a lack of information (unaware of the need to return for MCV2, unaware of the need to return for MCV2, and the place and/or time of immunization unknown). Hence, enhancing awareness about vaccine-preventable diseases, shortening the average time for vaccination at the health facility by half an hour, creating an alerting mechanism for MCV2 appointments, and future studies on the effect of healthcare provider-related factors on MCV2 uptake are recommended.